2022
DOI: 10.1038/s41467-022-34222-8
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cell differentiation status correlates with the feasibility of sustained unresponsiveness following oral immunotherapy

Abstract: While food allergy oral immunotherapy (OIT) can provide safe and effective desensitization (DS), the immune mechanisms underlying development of sustained unresponsiveness (SU) following a period of avoidance are largely unknown. Here, we compare high dimensional phenotypes of innate and adaptive immune cell subsets of participants in a previously reported, phase 2 randomized, controlled, peanut OIT trial who achieved SU vs. DS (no vs. with allergic reactions upon food challenge after a withdrawal period; n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Although this work addresses its role in cancer, SUSD2 may also regulate immune responses in allergic reactions. In fact, we believe that further research could be conducted in this context because CD8 + T cells were demonstrated to enhance allergic responses through the interaction with T helper type 2 cells 6 . In addition, SUSD2 was shown to be transcriptionally downregulated in atopic dermatitis skin lesions, 7 which could potentially promote allergen‐specific CD8 + T‐cell responses by removing SUSD2‐dependent T‐cell inhibitory regulation.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…Although this work addresses its role in cancer, SUSD2 may also regulate immune responses in allergic reactions. In fact, we believe that further research could be conducted in this context because CD8 + T cells were demonstrated to enhance allergic responses through the interaction with T helper type 2 cells 6 . In addition, SUSD2 was shown to be transcriptionally downregulated in atopic dermatitis skin lesions, 7 which could potentially promote allergen‐specific CD8 + T‐cell responses by removing SUSD2‐dependent T‐cell inhibitory regulation.…”
Section: Figurementioning
confidence: 97%
“…In fact, we believe that further research could be conducted in this context because CD8 + T cells were demonstrated to enhance allergic responses through the interaction with T helper type 2 cells. 6 In addition, SUSD2 was shown to be transcriptionally downregulated in atopic dermatitis skin lesions, 7 which could potentially promote allergen-specific CD8 + T-cell responses by removing SUSD2-dependent T-cell inhibitory regulation. Interestingly, surface SUSD2 expression has been recently detected in lung mast cells 8 correlating with their size and granularity, which might relate to an increased activation.…”
Section: Susd2-il-2 Receptor Interaction Hinders Antitumoral Cd8 + T-...mentioning
confidence: 99%
“…The potential mechanisms behind this cell reduction remain unclear, although deletion, anergy, and exhaustion may all contribute ( 44 ). There was a notable decrease in the frequencies of IL-4 + , IL-9 + , and IL-10 + peanut-reactive CD4 + T cells among total CD4 + T cells in peanut-allergic individuals following OIT ( 47 ). Additionally, it was discovered that, compared with desensitization, higher frequencies of both IL-4 + CD4 + T cells and IFN-γ + CD4 + T cells post-OIT displayed a significant negative correlation with sustained unresponsiveness ( 47 ).…”
Section: Mechanisms Of Oral Immunotherapy and Low-dose Oral Immunothe...mentioning
confidence: 99%
“…There was a notable decrease in the frequencies of IL-4 + , IL-9 + , and IL-10 + peanut-reactive CD4 + T cells among total CD4 + T cells in peanut-allergic individuals following OIT ( 47 ). Additionally, it was discovered that, compared with desensitization, higher frequencies of both IL-4 + CD4 + T cells and IFN-γ + CD4 + T cells post-OIT displayed a significant negative correlation with sustained unresponsiveness ( 47 ). Meanwhile, there was a significant reduction in the Th2-polarization surrogate marker OX40 expression in CD4 + T cells in peanut-allergic individuals after desensitization ( 47 ).…”
Section: Mechanisms Of Oral Immunotherapy and Low-dose Oral Immunothe...mentioning
confidence: 99%
See 1 more Smart Citation